2013
DOI: 10.1149/05004.0251ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Si Nanowire Technology

H. Iwai

Abstract: Recently, CMOS downsizing has been accelerated very aggressively in both production and research levels. However, it is still questionable if we can successfully introduce deep sub-10 nm CMOS LSIs into market, due to performance concerns -such as I on /I off ratio, current drive, variation in the electrical characteristics, concerns for the yield, reliability and manufacturing cost. We have conducted nano-CMOS studies in advance to provide possible solutions to the future expected problems. Si Nanowire FETs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, it is experimentally demonstrated that thermal conductivity of Si nanowire (SiNW) is reduced by one to two decades as compared with that of bulk, resulting in a great enhancement of the figure of merit as thermoelectric material. 5 Meanwhile, the SiNW MOSFET 7,8 suffers from heat generated in the device and requires a rapid heat dissipation rate within the system. Therefore, it is required to understand and predict a realistic picture of the complicated thermal transport process in nanostructured Si, which is governed by phonons and their energy dispersion and interactions.…”
mentioning
confidence: 99%
“…For example, it is experimentally demonstrated that thermal conductivity of Si nanowire (SiNW) is reduced by one to two decades as compared with that of bulk, resulting in a great enhancement of the figure of merit as thermoelectric material. 5 Meanwhile, the SiNW MOSFET 7,8 suffers from heat generated in the device and requires a rapid heat dissipation rate within the system. Therefore, it is required to understand and predict a realistic picture of the complicated thermal transport process in nanostructured Si, which is governed by phonons and their energy dispersion and interactions.…”
mentioning
confidence: 99%
“…Silicon nanowire (SiNW) is a promising candidate for nextgeneration materials such as gate-all-around field-effect transistors (FETs), [1][2][3] solar cells 4,5) and so on. Moreover, SiNW is expected to be a new material for thermoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nanowires (Si NWs) are promising candidates for the channel structure of next-generation transistors such as the surrounding gate field-effect transistors (FETs). [1][2][3] By adopting the Si NW structure for the surrounding gate FETs, the short-channel effect and power consumption are reduced effectively by downsizing the CMOS devices. 4,5) Moreover, Si NWs are expected to be a new thermoelectronic material with excellent performance owing to their low dimensionality.…”
Section: Introductionmentioning
confidence: 99%